Examining the opportunities and potential of Artificial Intelligence in national security and defence - Dražen Smiljanić (Strategos, 2023)
Artificial Intelligence (AI) is recognised as a disruptive technology that rapidly changes a wide range of businesses and industries. It also can transform functions (processes and systems) related to national security and defence. Although it is not primarily being developed in the defence sector, AI is poised to change the character of future conflict by improving the effectiveness, efficiency and speed of defence-related activities. However, while AI has enormous potential to replace or assist human factors in decision-making, it still cannot replace humans in strategic thinking. The paper first reviews the meaning, current developments, and challenges related to AI technology. It then scrutinises the impact of AI on national security and defence in three areas: defence capabilities, decision making and strategic thinking. The article concludes with a prospect on AI in general and in the security and defence domain, expecting its most significant value in support of decision-making.